Effect of long term tea cultivation in soil quality in deep, fine loamy, well drained soil of Jorhat district, Assam - BARUAH, NANDITA; MEDHI, B. K.; BORAH, NILAY; BARUAH, A. M.; SAIKIA, G. K. (Journal of Soil and Water Conservation, 2020)
Tea (Camellia sinensis) is one of the most important perennial cash crops of Assam used for domestic consumption and export. The investigation was undertaken to identify the Minimum data Set (MDS) for Soil Quality Index (SQI) assessment in the long term tea cultivation systems. Soil quality index (SQI) calculated for different categories of tea soils under continuous tea cultivation was observed to be highest in the category where tea cultivation was practiced in less than 15 years. In deep, fine loamy well drained soil, SQI was 14.11 for less than 15 years of continuous tea cultivation, 10.35 for 15-30 years, 12.15 for 30- 45 years, 10.28 for 45-60 years of continuous tea cultivation and 8.04 for more than 60 years. Through principal component analysis, the most sensitive soil quality indicators identified in deep, fine loamy, well drained soil were available nitrogen (Av N) for less than 15 years and 45 -60 years of continuous tea cultivation, total nitrogen (TN) for 15-30 years and 30-45 years and exchangeable Ca (Ex Ca) for more than 60 years of continuous tea cultivation.